Paul Ricœur and Metaphysics - Barnabas Aspray (Études Ricoeuriennes / Ricoeur Studies)
In twentieth-century France, the word “metaphysics” had connotations of closed systems which claimed certainty for themselves. As a result, few dared to engage in metaphysical speculation. Ricœur, however, rejected this prevalent definition because he believed it came from Heidegger’s procrustean reading of the history of philosophy. While agreeing that certainty and closure were neither desirable nor possible, Ricœur did make metaphysical claims. Following Jaspers’s revival of pre-modern apophatic metaphysics for which transcendence cannot be comprehended, Ricœur, in his early work, argued for “critical realism” against neo-Kantian idealism, “original affirmation” against Sartrean negativity, and the “metaphysical choice” of human freedom’s consent to the unchosen features of reality.